2015
DOI: 10.1210/en.2014-2012
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Regulates Puberty Onset and Fertility in the Female Mouse

Abstract: Puberty is a tightly regulated process that leads to reproductive capacity. Kiss1 neurons are crucial in this process by stimulating GnRH, yet how Kiss1 neurons are regulated remains unknown. Substance P (SP), an important neuropeptide in pain perception, induces gonadotropin release in adult mice in a kisspeptin-dependent manner. Here, we assessed whether SP, through binding to its receptor NK1R (neurokinin 1 receptor), participates in the timing of puberty onset and fertility in the mouse. We observed that 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 54 publications
6
52
0
Order By: Relevance
“…Simavli et al [179] found that agonism of NK1 receptors led to early onset of puberty. Similarly, absence of the Tac1 gene (which encodes Substance P) led to delayed puberty onset and subfertility in female mice [179].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
See 2 more Smart Citations
“…Simavli et al [179] found that agonism of NK1 receptors led to early onset of puberty. Similarly, absence of the Tac1 gene (which encodes Substance P) led to delayed puberty onset and subfertility in female mice [179].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…Simavli et al [179] found that agonism of NK1 receptors led to early onset of puberty. Similarly, absence of the Tac1 gene (which encodes Substance P) led to delayed puberty onset and subfertility in female mice [179]. Using Tac1 knockout mice, Niedermair et al [180] observed that Substance P deficiency is associated with decreased bone formation.…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
See 1 more Smart Citation
“…The lists of genes with sex-related expression patterns in pituitary and adrenal overlap substantially (40 of the top 200 genes in common) and include several molecules with functions in reproduction or in biological processes with a marked sex bias. Tissue-specific examples include, for pituitary, TAC1, encoding substance P, which regulates puberty onset and fertility 27 and PTGER2 which plays a role in ovulation and fertilization 28 , and, for adrenal, PRL, which stimulates lactation in new mothers, plays a role in social behaviors, and is regulated by adrenal steroids 29 .…”
Section: Multi-tissue Expression Data: Variation By Age and Sexmentioning
confidence: 99%
“…In addition to NKB, the SP/NK1R system also participates in the central regulation of the gonadotropic axis, likely via kisspeptin-dependent mechanisms (9, 10). Supporting this contention, ( a ) studies in humans, rabbits and rats showed a central stimulatory role of SP on LH release (11-13); ( b ) Kiss1 neurons are activated by SP (9); ( c ) SP mRNA and protein has been found in the ARC of rodents (10, 14); ( d ) SP immunoreactivity has been detected in Kiss1 and NKB neurons in the human infundibular nucleus (15); ( e ) chronic SP administration advances puberty onset in rodents (16) and ( f ) Tac1 KO mice with congenital absence of SP, display delayed puberty onset and reproductive impairments (16, 17).…”
Section: Introductionmentioning
confidence: 99%